2014
DOI: 10.5897/sre2014.5824
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity and phytochemical screening of Acalypha wilkesiana (Euphorbiaceae) Mull Arg. roots in alloxan-induced diabetic rats

Abstract: The aim of this study was to investigate the anti-diabetic effects and biochemical parameters of methanol root extract of Acalypha wilkesiana Mull Arg. (MEAW) in alloxan-induced diabetic rats. The effect of the extract (200 and 400 mg/kg, p.o.) on fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT) level and liver glycogen content were investigated in alloxan-induced diabetic rats after 14 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Plants have been shown to have antidiabetic properties and have been used in traditional medicines in management of diabetes mellitus (Osadebe et al, 2014). Some medicinal plants with investigated antidiabetic potentials include; Ceiba pentandra ( Odoh et al, 2016), Acalypha wilkesiana ( Odoh et al, 2014),Acanthus montanus (Odoh et al, 2013), Abelmoschus moschatus (Liu et al, 2007),, Carum carvi (Eddouks et al, 2004), Acacia Arabica (Yasir et al, 2010), Allium cepa (Eidi et al, 2006), Andrographis paniculata (Dandu and Inamdar, 2009), Aegle maarmelose (Seema et al, 1996), Azadirachata indica (Chattopadhyay, 1996), Brassica juncea (Thirumalai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have been shown to have antidiabetic properties and have been used in traditional medicines in management of diabetes mellitus (Osadebe et al, 2014). Some medicinal plants with investigated antidiabetic potentials include; Ceiba pentandra ( Odoh et al, 2016), Acalypha wilkesiana ( Odoh et al, 2014),Acanthus montanus (Odoh et al, 2013), Abelmoschus moschatus (Liu et al, 2007),, Carum carvi (Eddouks et al, 2004), Acacia Arabica (Yasir et al, 2010), Allium cepa (Eidi et al, 2006), Andrographis paniculata (Dandu and Inamdar, 2009), Aegle maarmelose (Seema et al, 1996), Azadirachata indica (Chattopadhyay, 1996), Brassica juncea (Thirumalai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Arg. of leaves and roots have been reported in some recent studies (12,14,15), the underlying mechanisms behind these effects and phytochemical constituents of different parts of this plant are not fully understood.…”
mentioning
confidence: 99%
“…Odoh et al (14) and Olukunle et al (12) reported the antidiabetic and hypoglycemic as well as hypolipidemic activities of root and leaf extracts, respectively, in alloxan-induced diabetic rats; however, stembark was not used in their studies and Odoh et al (14) only qualitatively determined the phytochemical constituents in root extracts. Furthermore, Igwe et al (16) only analyzed the leaf ethanolic extract to identify its bioactive compounds by using GC-MS while other parts of the plant were not analyzed.…”
mentioning
confidence: 99%
See 2 more Smart Citations